Street smart : intelligence preparation of the battlefield for urban operations - Medby, Jamison Jo; Glenn, Russell W. (Rand, 2002)
Urban operations are highly complex because of the multitudes of people and structures as well as the density of the city?s infrastructure. These same features complicate the intelligence and decisionmaking processes associated with military operations at the strategic, operational, and tactical levels of war. Intelligence preparation of the battlefield (IPB), the Army?s longstanding methodology for incorporating and analyzing relevant information for all types of operations, is currently not effective for tackling the operational and intelligence challenges of urban operations. This study.